Gazdasági és politikai elemek a II. Orbán-kormány gazdaságpolitikájában - Gősi, János (Jelenkori Társadalmi és Gazdasági Folyamatok, 2011)
The economical and political elements of the economic policy of II. Orbán-government Taxes crisis: banking, commerce, etc.. The flat-rate personal income tax Compulsory membership of private pension funds nationalization of assets The retail price for repayment of residential foreign currency loans recorded a large loss for the banks II. Orbán government's economic policy for international confidence decreased. The hungarian government bonds and interest rates in November 2011 increased to 8.5% This category is higher than the trumpery of Romania To establish the permanent development it is necessary to employ more: the efficient reform of systems of budget, public administration, education, public health and social welfare.